DEVELOPING STUDENTS’ ABILITY OF MATHEMATICAL CONNECTION THROUGH USING OUTDOOR MATHEMATICS LEARNING - Saleh Haji; M Ilham Abdullah; Syafdi Maizora; Yumiati Yumiati (Jurnal Infinity, 2017)
The Purpose of this study is to determine the achievement and improvement of students’ mathematical connectionability through using outdoor mathematics learning. 64 students from the fifth grade of Primary School at SDN 65 and SDN 67 Bengkulu City were taken as the sample of this study. While the method of the research used in this research is experiment with quasi-experimental designs non-equivalent control group. The results of the study are as follows: (1) There is an increasing ability found in mathematical connection of students whom taught by using outdoors mathematics learning is 0,53; (2) Based on statical computation that achievement of students’ ability of mathematical connection is taught by using outdoor mathematics learning score is 71,25. It is higher than the students score 66,25 which were taught by using the conventional learning. So as to improve students’ mathematical connection, teachers are suggested to use the outdoors mathematics learning